Protests, Long-term Preferences, and Populism. Evidence from 1968 in Europe - Andrea Fazio (Global Labor Organization (GLO), 2023)
In 1968, young people grew up in an atmosphere of strong dissatisfaction and distrust against the status quo. We show that higher exposure to protests in 1968 leads to higher dissatisfaction toward national governments and raises the probability of voting for populist parties. Consistently with the impressionable years hypothesis, we find these effects valid only for those aged between 18 and 25 during 1968. Our results are robust to a series of placebo tests and to alternative definitions of our treatment and control groups. We find that our results are driven by individuals with a middle or low level of education. We also find suggestive evidence that the mechanisms driving our results can depend on individuals' level of education: within our treated cohort people with an elementary level of education appear more attracted by the populist rhetoric, while people with a middle level of education are more likely to care about traditional values.
Keywords: P16; D72; Z10; 330; Populism; 1968 Protests; Log-term Preferences; Impressionable years